'Did queer Muslims even exist?' – racialised grids of intelligibility in Swedish LGBTQ contexts. (3rd March 2020) - Kehl, Katharina
ABSTRACT: This article explores racialised grids of intelligibility around gender identity and sexuality in white Swedish LGBTQ contexts. By analysing personal stories shared on a separatist Instagram account by and for LGBTQ people racialised as non-white and/or Muslim, the article identifies some of the predominant narratives through which they become intelligible, both to other people and to themselves. Four frameworks are particularly recurring: the notion of them being victims of a 'hateful other', strong expectations to come out, exotification and tokenism (both sexualised and otherwise), and a general lack of representation. I argue that all of these revolve around notions of LGBTQ people racialised as non-white and/or Muslim as never quite belonging and thus never quite recognisable. They are instead frequently situated between white, gender-equal and LGBTQ-friendly 'Swedishness' and threatening, LGBTQ-phobic racialised 'others', made intelligible only in relation to either of these.